Pemphigus: Current treatment, challenges in the treatment and our clinical experience [Pemfigus: Güncel tedavi, karşilaşilan zorluklar ve klinik deneyimlerimiz] - (:unkn) unknown (My University, 2008)
Pemphigus vulgaris is a rare disease. Systemic corticosteroids are the mainstay of therapy, however, long-term treatment with high-dose steroids may be associated with many serious side effects. Majority of patients are prescribed adjuvant treatments in order to reduce the need for steroid use. Immunsuppressive agents like azathioprine, cyclophosphamide, methotrexate and cyclosporine, antiinflammatory drugs such as gold, dapsone and tetracycline, plasmapheresis, photopheresis, high dose intravenous immunglobuline and recently, immunmodulatuar agents like rituximab (anti CD20 monoclonal antibody) and TNF-α antagonists are among the adjuvant treatments. We report here the results of 8-years of follow-up in 36 patients with pemphigus vulgaris.
Keywords: Clinical experience; Current treatment; Pemphigus; Treatment